2011
DOI: 10.1073/pnas.1114023109
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila regulates the small GTPase Rab1 activity by reversible phosphorylcholination

Abstract: Effectors delivered into host cells by the Legionella pneumophila Dot/Icm type IV transporter are essential for the biogenesis of the specialized vacuole that permits its intracellular growth. The biochemical function of most of these effectors is unknown, making it difficult to assign their roles in the establishment of successful infection. We found that several yeast genes involved in membrane trafficking, including the small GTPase Ypt1, strongly suppress the cytotoxicity of Lpg0695… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
179
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(186 citation statements)
references
References 38 publications
1
179
0
Order By: Relevance
“…Interestingly, the intracellular pathogen L. pneumophila is well documented to hijack the function of Rab1 in infected cells by posttranslational modification of nearby switch II residues, including adenylylation, also known as AMPylation, of Y80 and phosphocholination of S79 (Fig. 3D) (15,16,28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the intracellular pathogen L. pneumophila is well documented to hijack the function of Rab1 in infected cells by posttranslational modification of nearby switch II residues, including adenylylation, also known as AMPylation, of Y80 and phosphocholination of S79 (Fig. 3D) (15,16,28).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have shown that phosphocholination and AMPylation of Rab1 switch II manipulate Rab1 function by blocking the ability of Rab1 to interact with GEFs and GAPs (16,28,30), because switch II serves as the primary interface for these binding events. To investigate whether phosphorylation of Rab1T75 may have a similar effect, we assayed the ability of the Legionella Rab1 GEF DrrA (GEF domain only, residues 340-533) to catalyze the displacement of mant-GDP from WT and mutant Rab1 in vitro (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the case of adenylylation, there was a major effect on the interaction with GDI, which was essentially abolished and would therefore lead to stabilization of membrane attachment, and in this case preferentially in the inactive form due to the preference of the phosphocholination reaction for Rab : GDP. Similarly to the situation with adenylylation, L. pneumophila also secretes a protein that can reverse the modification, in this case removing the phosphocholine group hydrolytically (Tan et al, 2011;Goody et al, 2012). The similarity with adenylylation also extends to the present lack of understanding of the biological purpose of the modification, apart from the general feature that Rabs are stabilized in their membrane-bound form.…”
Section: Learning About Vesicular Transport From Bacteriamentioning
confidence: 97%
“…Phosphocholination could however affect the interaction with GEFs, as shown for phosphocholinated Rab35 and its GEF connecdenn (15). However, interestingly, Legionella also expresses a dephosphorylcholinase, Lgp0696, that can reverse AnkX-mediated modification of Rab1 (17), and thus possibly permits binding of Rab1 to its GEF(s). Posttranslational modifications of Rab GTPases represent a tentative mechanism to explain, at least in part, how Rab GTPases can be targeted to membranes.…”
mentioning
confidence: 99%